Soybean oil is not allergenic to soybean-sensitive individuals - Bush, Robert K.; Taylor, Steve L.; Nordlee, Julie A.; Busse, William W. (Journal of allergy and clinical immunology, 1985)
We have previously demonstrated that peanut oil is not allergenic to peanut-sensitive individuals. Seven soybean-sensitive patients were enrolled in a double-blind crossover study to determine whether ingestion of soybean oil can induce adverse reactions in such patients. All subjects had histories of systemic allergic reactions (urticaria, angioedema, wheezing, dyspnea, and/or vomiting) after soybean ingestion and had positive puncture skin tests with a 1:20 w v glycerinated-saline whole soybean extract. Sera from six of the seven subjects were tested by RAST assay for the presence of specific IgE antibodies to soybean allergens. All patients had elevated levels of serum IgE antibodies to the crude soybean extract: binding values ranged from 2.3 to 28.1 times that of a negative control serum. Before the oral challenges, all patients demonstrated negative puncture skin tests to three commercially available soybean oils and to olive oil (control). On four separate days, patients were challenged with the individual soybean oils and olive oil in random sequence. At 30-minute intervals, under constant observation, patients ingested 2, 5, and 8 ml of one of the soybean oils or olive oil contained in 1 ml capsules. No untoward reactions were observed with either the commercially available soybean oils or olive oil. Soybean oil ingestion does not appear to pose a risk to soybean-sensitive individuals.